LEMAHNYA PENEGAKAN HUKUM DI INDONESIA DARI SUDUT PANDANG STRUKTURAL - Adriani Adnani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
As a body politic was wally of course that law constitutes 17 state base. Its fact is oftentimes jurisdidional is ruled out, there are Many deViatiOn happening qf what does be expected. Most more if concerns by aught structural facet. Of this structural viewpoint really appears really how its frail law at Indonesian.